Abnormal vascular network complexity: a new phenotypic marker in hereditary non-polyposis colorectal cancer syndrome. Issue 12 (21st November 2003) - De Felice, C; Latini, G; Bianciardi, G; Parrini, S; Fadda, G M; Marini, M; Laurini, R N; Kopotic, R J
Abstract : Background: Hereditary non-polyposis colorectal cancer (HNPCC) (Lynch cancer family syndrome I (LCFS1) and II (LCFS2)) is one of the most common hereditary cancer disorders. HNPCC results from dominantly inherited germline mutations in mismatch repair (MMR) genes, leading to genomic instability and cancer. No predictive physical signs of HNPCC are available to date. Aims: Increased complexity in tumour associated vascular growth has been reported. Here, we tested the hypothesis that an increased vascular network complexity is a phenotypic marker for LCFS2. Methods: Fourteen subjects from an LCFS2 kindred (gene carriers, n = 5; non-carriers, n = 9) and 30 controls were examined. Fractal dimension ( D ) at two scales ( D ( 1–46 ), and D ( 1–15 ), tortuosity (minimum path dimension, Dmin), and relative Lempel-Ziev complexity (L-Z) of the vascular networks from the lower gingival and vestibular oral mucosa were measured. Results: LCFS2 networks exhibited a significantly increased overall complexity at both larger ( D ( 1–46 ): 1.82 (0.04) v 1.68 (0.08); p < 0.0001) and smaller ( D ( 1–15 ): 1.51 (0.11) v 1.20 (0.09); p < 0.0001) scales, increased destructured randomness (L-Z: 0.77 (0.09) v 0.56 (0.03); p < 0.0001), and decreased vessel tortuosity ( Dmin : 1.02 (0.03) v 1.07 (0.04); p = 0.0005) compared with control patterns. The vascular networks of LCFS2 gene carriers showed higher complexity at the smaller scale ( D ( 1–15 ): 1.59 (0.12) v 1.47 (0.07); p = 0.034), and higher destructured randomness (L-Z: 0.85 (0.11) v 0.73 (0.05); p = 0.013) than those of non-carriers. Conclusions: Increased oral vascular network complexity is a previously unrecognised phenotypic marker for LCFS2, and is related to gene mutation carrier status.